Human Capital Investment’s Contribution Towards Economic Growth in Malawi - Milanzi, S. A. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Human capital investment is viewed as one of the drivers of social development and industrial growth in every country. It enriches the poor and the inferior groups in the economy as it equips them with equal opportunities to take part in local and national development. The purpose of this study was to investigate the effects of Human capital investment on economic growth in Malawi by means of the annual time series data covering the period 1995 to 2017 obtained from the World Bank website. The study employs the Autoregressive Distributed Lag (ARDL) to estimate the link between the variables. This approach was found to be relevant because of its ability to generate robust and reliable results even if the sample size is small or finite like in the case of this study. Literature review evidence has revealed that there are limited studies done in this area in the context of Malawi. Therefore, this paper aims to contribute to this research gap and also to contribute to the policy formulation in the relationship between human capital investment proxied by government expenditures on education and health sectors and economic growth. The empirical results showed that total government expenditure on public and private education has a negative relationship with growth whilst total government expenditure on health sector is positive. Based on this, the study recommends that the government has to balance between education and health expenditures as the main route towards growth. The study supports the projection of budget structure in the year 2016-2017 towards education and health sectors.
Journal article published in the International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: ARDL; Education; Government Expenditure; Health; Human Capital Investment; Labour; Saving and investment -- Malawi; Capital budget